(x-7)(x-2)(x-4)(x-5)=7x

Simple and best practice solution for (x-7)(x-2)(x-4)(x-5)=7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-7)(x-2)(x-4)(x-5)=7x equation:


Simplifying
(x + -7)(x + -2)(x + -4)(x + -5) = 7x

Reorder the terms:
(-7 + x)(x + -2)(x + -4)(x + -5) = 7x

Reorder the terms:
(-7 + x)(-2 + x)(x + -4)(x + -5) = 7x

Reorder the terms:
(-7 + x)(-2 + x)(-4 + x)(x + -5) = 7x

Reorder the terms:
(-7 + x)(-2 + x)(-4 + x)(-5 + x) = 7x

Multiply (-7 + x) * (-2 + x)
(-7(-2 + x) + x(-2 + x))(-4 + x)(-5 + x) = 7x
((-2 * -7 + x * -7) + x(-2 + x))(-4 + x)(-5 + x) = 7x
((14 + -7x) + x(-2 + x))(-4 + x)(-5 + x) = 7x
(14 + -7x + (-2 * x + x * x))(-4 + x)(-5 + x) = 7x
(14 + -7x + (-2x + x2))(-4 + x)(-5 + x) = 7x

Combine like terms: -7x + -2x = -9x
(14 + -9x + x2)(-4 + x)(-5 + x) = 7x

Multiply (14 + -9x + x2) * (-4 + x)
(14(-4 + x) + -9x * (-4 + x) + x2(-4 + x))(-5 + x) = 7x
((-4 * 14 + x * 14) + -9x * (-4 + x) + x2(-4 + x))(-5 + x) = 7x
((-56 + 14x) + -9x * (-4 + x) + x2(-4 + x))(-5 + x) = 7x
(-56 + 14x + (-4 * -9x + x * -9x) + x2(-4 + x))(-5 + x) = 7x
(-56 + 14x + (36x + -9x2) + x2(-4 + x))(-5 + x) = 7x
(-56 + 14x + 36x + -9x2 + (-4 * x2 + x * x2))(-5 + x) = 7x
(-56 + 14x + 36x + -9x2 + (-4x2 + x3))(-5 + x) = 7x

Combine like terms: 14x + 36x = 50x
(-56 + 50x + -9x2 + -4x2 + x3)(-5 + x) = 7x

Combine like terms: -9x2 + -4x2 = -13x2
(-56 + 50x + -13x2 + x3)(-5 + x) = 7x

Multiply (-56 + 50x + -13x2 + x3) * (-5 + x)
(-56(-5 + x) + 50x * (-5 + x) + -13x2 * (-5 + x) + x3(-5 + x)) = 7x
((-5 * -56 + x * -56) + 50x * (-5 + x) + -13x2 * (-5 + x) + x3(-5 + x)) = 7x
((280 + -56x) + 50x * (-5 + x) + -13x2 * (-5 + x) + x3(-5 + x)) = 7x
(280 + -56x + (-5 * 50x + x * 50x) + -13x2 * (-5 + x) + x3(-5 + x)) = 7x
(280 + -56x + (-250x + 50x2) + -13x2 * (-5 + x) + x3(-5 + x)) = 7x
(280 + -56x + -250x + 50x2 + (-5 * -13x2 + x * -13x2) + x3(-5 + x)) = 7x
(280 + -56x + -250x + 50x2 + (65x2 + -13x3) + x3(-5 + x)) = 7x
(280 + -56x + -250x + 50x2 + 65x2 + -13x3 + (-5 * x3 + x * x3)) = 7x
(280 + -56x + -250x + 50x2 + 65x2 + -13x3 + (-5x3 + x4)) = 7x

Combine like terms: -56x + -250x = -306x
(280 + -306x + 50x2 + 65x2 + -13x3 + -5x3 + x4) = 7x

Combine like terms: 50x2 + 65x2 = 115x2
(280 + -306x + 115x2 + -13x3 + -5x3 + x4) = 7x

Combine like terms: -13x3 + -5x3 = -18x3
(280 + -306x + 115x2 + -18x3 + x4) = 7x

Solving
280 + -306x + 115x2 + -18x3 + x4 = 7x

Solving for variable 'x'.

Reorder the terms:
280 + -306x + -7x + 115x2 + -18x3 + x4 = 7x + -7x

Combine like terms: -306x + -7x = -313x
280 + -313x + 115x2 + -18x3 + x4 = 7x + -7x

Combine like terms: 7x + -7x = 0
280 + -313x + 115x2 + -18x3 + x4 = 0

The solution to this equation could not be determined.

See similar equations:

| p-0.6*30=19 | | (5X^3+x^2+x-13)(x^2-1)= | | (2m-7n)(2m-3n)= | | -9(-2r-10s+3)= | | 2Inx-5Inx=6 | | 3x-1x+4x+13=180 | | 8(c-6)= | | (4x^2-6)(7x^2-7)= | | 5-3/2(6-2/3y) | | 13(x+5)= | | 3x+2=5x-18 | | y=3x^3-7x^2-14x+24 | | log5[5x/x-2]=2 | | 3b-5b=10 | | 3.25b-1.5=14.5 | | 3.25-1.5=14.5 | | 3(x-7)=63 | | Ln(x)=-90 | | 3(c-4)=3c-12 | | -6p+8+7p=12 | | 7r^2+10r-72=0 | | 2w=36+5w | | 7r^2+10-72=0 | | 3y+15x=-24 | | 100+10xlog=60 | | 3x-3x-4=4 | | 2t-S=2u | | 6y-48=8 | | 4x=-2x-8 | | -9-4(-11)= | | -11x+4=62 | | 2ln(x+1)=ln(x^2-1) |

Equations solver categories